Strengthening Resilience to Ensure Cybersecurity in Local Communities - Bernik, Igor (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
In today’s digital environment, local communities are increasingly confronted with complex cybersecurity challenges that extend beyond the technical domain and encompass intricate social, organisational, and security dimensions. This paper draws on the concept of resilience and applies it to cybersecurity in local settings. It presents the key elements that influence the ability of local communities to detect, prevent, respond to, and recover from cyber incidents. Social factors such as digital inclusion, trust in local institutions, crisis communication, and the role of civil protection are analysed. Integrating social science approaches into developing local cybersecurity strategies is essential; therefore, this paper offers guidelines for building (cyber) resilient and secure local environments.